Distinct Effects of Antidepressants in Association With Mood Stabilizers and/or Antipsychotics in Unipolar and Bipolar Depression. Issue 2 (24th March 2022) - Moderie, Christophe; Nuñez, Nicolas; Comai, Stefano; Saint-Laurent, Marie; Fielding, Allan; Low, Nancy; Gobbi, Gabriella
Abstract: Purpose/Background: There is a dearth of studies comparing the clinical outcomes of patients with treatment-resistant unipolar (TRD) depression and depression in bipolar disorder (BD) despite similar treatment strategies. We aimed to evaluate the effects of the pharmacological combinations (antidepressants [AD], mood stabilizers [MS], and/or antipsychotics [AP]) used for TRD and BD at the McGill University Health Center. Methods/Procedures: We reviewed health records of 206 patients (76 TRD 130 BD) with TRD and BD treated with similar augmentation strategies including AD with MS (AD+MS) or AP (AD+AP) or combination (AD+AP+MS). Clinical outcomes were determined by comparing changes on the 17-time Hamilton Depression Rating Scale (HAMD-17), Quick Inventory of Depressive Symptomatology, and Clinical Global Impression-Severity of Illness at the beginning (T0) and after 3 months of an unchanged treatment (T3). Findings/Results: Baseline HAMD-17 scores in TRD were higher than in BD ( P < 0.001), but TRD patients had a greater improvement at end point ( P = 0.003). Antidepressants with AP generated greater reductions in HAMD-17 in TRD compared with BD ( P = 0.02). Importantly, in BD patients, the addition of AD compared with other treatment strategies failed to improve the outcome. The limitations of this study include possibly unrepresentative subjects from tertiary care settings, incomplete matching of BD and TRD subjects, nonrandomized treatment with unmatched agents, doses, and times, unknown treatment adherence, and nonblinded retrospective outcome assessments. Nevertheless, the findings may reflect real-world interactions of clinically selected pharmacotherapies. Implications/Conclusions: Combination of augmentation strategies such as AD+AP and/or MS showed a better clinical improvement in patients with TRD compared with BD suggesting a limited evidence for AD potentiation in BD.